The Adverse Effects of British Colonialism on the Culture and Psychology of the Indians: A Postcolonial Study (Green University Review of Social Sciences, 2022)
Colonization implies an all-inclusive and all-pervasive process that brings under its occupation not only the land and wealth of the colonized country but exercises domination over all facets of the life of the people – economic, political, social, educational, cultural and psychological in their exteriors and interiors. With full knowledge of how to perpetrate the colonial rule on the colony permanently, the British colonizers went for superimposition of their own culture on the culture of the colonized with the colonized ultimate object of destroying the native age-old and proverbially rich culture of India. Education being the sure and certain weapon to win the battle of superimposition of a certain culture upon another, the colonialists clamped down an Education Policy on the Indians – a policy potent enough to subjugate the Indians under the yoke of colonialism. They propagated their culture through various cultural mediums including dramatic productions, particularly “promoting Shakespeare’s work in colonial Calcutta reproducing the metropolitan culture as a part of the civilizing mission of the British Raj (Sing, 1996, P. 122). The conquest of the civilizational mission of the British Raj so disrupted the cultural and psychological aspects of the life of the Indians (Bangalis) that the elite (so-called advanced section of the population) gloated in the thought that the colonizers had rescued them from backwardness and it was their duty to prop them in all ways possible to continue their regime free from opposition, intervention and rebellion. This was how colonialism throve on the subservient mindset of the privileged class resulting in the prolongation in the sub-continent of the British domination that had to be annihilated by waging tremendous struggle by the people who could not be gained over by the rosy picture of immense prospects hung up by the colonizers.Green University Review of Social Sciences Dec 2021; 7(1-2): 22-34